Critical making with a raspberry pi ‐ towards a conceptualization of librarians as makers. Issue 1 (2014) - Parham, Krista E.; Ferri, Anna M.; Fan, Stephanie; Murray, Matthew P.; Lahr, Rebecca A.; Grguric, Ekatarina; Swamiraj, Monica; Meyers, Eric
ABSTRACT: Makerspaces, designated spaces to foster creativity and technology skills, are increasingly being incorporated into libraries. Although makerspaces in libraries are depicted positively in the literature and are praised by professional organizations, there is little exploration of the acculturation that results as libraries and makerspaces learn to coexist. In keeping with Matt Ratto's model of "critical making, " we used the process of collaboratively building an interactive Readers' Advisory Device (RAD) that runs on a Raspberry Pi computer to elicit introspection. In this poster we describe how our interdisciplinary group faced challenges working with unfamiliar tools and technology through a non‐hierarchical, collaborative, and iterative process, seeking knowledge and skills from the maker community. We then engaged the wider community around both how and why we developed this device by exhibiting it at a Maker Faire. Our experience taught us about the making process and helped us think critically about the intersection of libraries and makerspace cultural values. We found that making is as much an act of networking as of creation.